Glycation and inactivation of sorbitol dehydrogenase in normal and diabetic rats. - Hoshi, A (1996)
Sorbitol dehydrogenase (SDH) is involved in the polyol pathway, which plays an important role in the pathogenesis of diabetic complications. We have measured the tissue distributions of SDH mRNA, both the immunoreactive enzyme levels and the enzyme activity. SDH mRNA was especially abundant in liver, kidney and testis. Both the activity and enzyme content are high in liver and kidney but not in testis. The discrepancy between mRNA and immunoreactive enzyme levels and the activity of SDH observed in testis was also seen in livers of streptozotocin-induced diabetic rats. SDH was found to exist in both glycated and non-glycated forms, with larger amounts of the glycated protein in the diabetic liver. Moreover, after incubation of purified enzyme with glucose or fructose, its activity was markedly decreased. These results indicate that glycation causes a decrease in SDH activity in liver under diabetic conditions. The same post-transcriptional event might occur to decrease the activity of SDH in testis in normal animals.